Magnetotelluric Imaging of the Central Himalayan Crust Away From Rift Zones - Gang Wang; Hui Fang; Qing Lei; Xinxue Xu; Hongda Liang; Yaoyang Zhang (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Imaging the crustal structure and state of the Himalayan Orogenic Belt (HOB) is of great significance for understanding crustal deformation and its tectonic response in the collision front of the Indian‐Eurasian plates. To avoid the influence from the anomalies underneath the north‐south trending rifts, a three‐dimensional electrical resistivity model across the central HOB was obtained between the Dingjie‐Shenzha and Yadong‐Gulu rifts. No lower‐crustal conductor was found in the southern Lhasa Terrane, and the lower crust with a moderate resistivity value of approximately 100 Ωm is interpreted to be the residue of previous partial melting beneath the Gangdese porphyry copper deposits. The middle crust between the Main Himalayan Thrust and Southern Tibet Detachment System is electrically resistive to the north of the north Himalayan gneiss domes (NHGD) belt and conductive to the south. The middle crust in the northern Himalayas may have undergone partial melting and crystallization during southward migration and duplexing. There is a strong deep‐shallow coupling relationship in the central HOB, where an increase in the underthrusting angle of the Indian crust has resulted in a southward turn of the NHGD belt.